First record of Buenia massutii Kovačić, Ordines, & Schliewen, 2017 in the Atlantic Ocean based on molecular and morphological evidences. (18th November 2019) - Ordines, Francesc; Ramírez‐Amaro, Sergio; Burgos, Candelaria; Baro, Jorge; Kovačić, Marcelo; Sobrino, Ignacio
Abstract: The recently described Mediterranean goby species, Buenia massutii, was found at the deep shelf in the Gulf of Cádiz (north‐eastern Atlantic Ocean). The identification of the specimen was performed using morphological analysis and molecular techniques; including the sequencing of the mitochondrial genes Cytochrome c Oxidase I ( DNA barcode ) and Cytochrome b. The sequences for Cytochrome b is presented for the first time for B. massutii . The limited migration capability and behaviour of small benthic gobies, the short lifespan of Buenia species, and the oceanographic characteristics of the Strait of Gibraltar suggest the existence of an independent Atlantic population of B. massutii .